Edukasi dan Simulasi Bantuan Hidup Dasar untuk Siswa - Fhauzia Iin Aldini; Kartika Purdani Setia Purdani; M Bachtiar Safrudin; Ajeng Irma Riana Dewi; Alfina Nurrahmawati; Alvinna Mavliani; Bunga Yusnanda; Farhan Muzzaki; Lutfi Nur Amalia; Muhammad Ridwan; Twy Kurmiantin; Yunisah Fitri (Jurnal Pengabdian Masyarakat Cendikia Jenius, 2025)
Emergencies such as sudden cardiac arrest can occur in the school environment and may lead to death if not treated immediately. Knowledge and skills in Basic Life Support (BLS) are essential for students to provide initial assistance before medical personnel arrive. This community service activity aimed to improve the knowledge and skills of eighth-grade students at SMP Negeri 1 Tenggarong through BLS education and simulation. The activity was conducted on September 24, 2025, involving 30 students. The methods used included interactive counseling, demonstrations, and hands-on practice of Cardiopulmonary Resuscitation (CPR) with pretest and posttest evaluations. The results showed a significant improvement in students’ ability to recognize signs of cardiac arrest and perform CPR correctly. This activity proved effective in increasing students’ awareness and preparedness in responding to emergency situations.